(untitled) (Jurnal Kemanusiaan, 2018)
The Quran’s tahfiz education has grown so rapidly in Malaysia due to the high demand of society, as well as the public’s awareness of the importance of memorizing the Koran. Selangor is among the states with the largest number of tahfiz institutions in Malaysia. These tahfiz institutions have different infrastructures and infrastructure according to their capabilities. There are some that may be categorized as perfect, but some others may still be categorized as deficient. Therefore, the objective of this study is to look at the forms of infrastructure found in private tahfiz institutions in Selangor based on the perception of teachers teaching at the institution. The method used in this study is a questionnaire instrument that is distributed to several randomly chosen respondents. It is hoped that the findings of this study will be given due attention by the authorities in the state of Selangor, in order to enhance and strengthen its status in line with its function of producing the generation of the al-Quran that is competitive and growing in line with current state of education.